2006
DOI: 10.1007/s10926-006-9021-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Sickness Absence in Patients with Chronic Low Back Pain: A Systematic Review

Abstract: No core set of predictors exists for sickness absence in general. The characteristics of the study including the decision to report sick or to return to work determined the influence of several predictors on sickness absence in patients with CLBP. Further research and use of a core set of measurements and uniform definitions are needed to predict sickness absence and return to work in patients with CLBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
99
1
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 74 publications
6
99
1
6
Order By: Relevance
“…The finding that expectations regarding RTW at baseline predict NRTW at 2 years is consistent with previous research in general injury cohorts [18][19][20][21][22][23][24][25][26] . This study is the first to demonstrate that this factor predicts RTW in a RTC cohort.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The finding that expectations regarding RTW at baseline predict NRTW at 2 years is consistent with previous research in general injury cohorts [18][19][20][21][22][23][24][25][26] . This study is the first to demonstrate that this factor predicts RTW in a RTC cohort.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that developing a screening tool to detect individuals at risk of NRTW would be beneficial, since appropriate and effective interventions to increase the RTW rate could be offered. The two-item measure is short (5-10 minutes to complete) and simple to administer and answer, meaning that non-specialists can easily score the items and determine whether someone is at-risk of NRTW.The finding that expectations regarding RTW at baseline predict NRTW at 2 years is consistent with previous research in general injury cohorts [18][19][20][21][22][23][24][25][26] . This study is the first to demonstrate that this factor predicts RTW in a RTC cohort.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…This corroborates with the evidence review for UK occupational health guidelines by Waddell and Burton. They found that the worker's own beliefs that their LBP was caused by their work and their own expectations about inability to RTW are particularly important [4,11,17,19,27]. A systematic review by Mondloch et al summarized the mechanisms by which expectations can affect outcomes [16].…”
Section: Discussionmentioning
confidence: 99%
“…28,29 There are indicators that competitive constructs can predict the occupational status to at least the same degree. 30,31 Especially patients' self-reported measures have been shown to be significant predictors of successful RTW. So far, 2 studies have confronted FCE-based predictions with self-reported measures: first, the self-reported pain intensity, 28 and second, the patient's expected disability in the job.…”
mentioning
confidence: 99%